To Evaluate the Groundwater Quality of Fatehgarh Sahib (International Journal of Innovative Research in Engineering & Management, 2022)
Models were built from 2020 to 2022 in  selected areas of the Fatehgarh district state (India) during  pre-rainstorm, post-tempest, spring, and winter seasons to  assess the impact of inadvertent examples on the quality of  groundwater. Using traditional evaluation techniques, the  idea of groundwater and its sensitivity to the framework of  water as well as a source of drinking water was surveyed.  According to delayed effects of evaluation, conductivity,  alkalinity, and hardness restrictions are better in the post storm season than in the spring season. Groundwater in the  spring, the winter, after a storm, and before a storm, An  EC of 910 to 1313 s/cm, a TDS of 659 All out  Disintegrated Strong, and a pH of 7.3 to 8.1 was the  norm.) The outcomes were contrasted with the drinking  water standard values set by the World Health  Organization (WHO, 2006). According to the review,  when compared to tests conducted before the precipitation, the majority of groundwater tests were found to be  inappropriate for the water system under the current storm.
Keywords: pH; Water Quality; Fatehgrah; Groundwater